Facile Synthesis of Brush Poly(phosphoamidate)s via One‐Pot Tandem Ring‐Opening Metathesis Polymerization and Atom Transfer Radical Polymerization. Issue 17 (14th April 2014) - Ding, Liang; Qiu, Jun; Wei, Jun; Zhu, Zhenshu
<x xml:space="preserve">Abstract</x> Poly(2‐(dimethylamino)ethyl methacrylate) (PDMAEMA)‐based brush poly(phosphoamidate)s are successfully synthesized by a combination of ring‐opening metathesis polymerization (ROMP) and atom transfer radical polymerization (ATRP) following either a commutative two‐step procedure or a straightforward one‐pot process using Grubbs ruthenium‐based catalysts for tandem catalysis. Compared with the traditional polymerization method, combining ROMP and ATRP in a one‐pot process allows the preparation of brush copolymers characterized by a relatively moderate molecular weight distribution and quantitative conversion of monomer. Moreover, the surface morphologies and aggregation behaviors of these polymers are studied by AFM and TEM measurements. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>